Therapeutic potential of urine exosomes derived from rats with diabetic kidney disease - Mishra, Deendayal Das; Sahoo, Biswajit; Maurya, Pramod Kumar; Sharma, Rajni; Varughese, Santosh; Prasad, Narayan; Tiwari, Swasti (Frontiers in Endocrinology, 2023)
Kidney disease are prevalent in diabetes. Urinary exosomes (uE) from animal models and patients with Diabetic nephropathy (DN) showed increased levels of miRs with reno-protective potential. We examined whether urinary loss of such miRs is associated with their reduced renal levels in DN patients. We also tested whether injecting uE can leverage kidney disease in rats. In this study (study-1) we performed microarray pro filing of miRNA in uE and renal tissues in DN patients and subjects with diabetes without DN (controls). In study-2, diabetes was induced in Wistar rats by Streptozotocin (i.p. 50 mg/kg of body weight). Urinary exosomes were collected at 6th, 7th and 8th weeks, and injected back into the rats (100ug/biweekly, uE-treated n=7) via tail vein on weeks 9and 10. Equal volume of vehicle was injected in controls (vehicle, n=7). uE from the human and rat showed the presence of exosome-specific proteins by immunoblotting. Microarray profiling revealed a set of 15 miRs having high levels in the uE, while lower in renal biopsies, from DN, compared to controls (n=5-9/group). Bioinformatic analysis also confirmed the Reno protective potential of these miRs. Taqman qPCR confirmed the opposite regulation of miR-200c-3p and miR-24-3p in paired uE and renal biopsy samples from DN patients (n=15), relative to non-DN controls. A rise in 28 miRs levels, including miR-200c-3p, miR-24-3p, miR-30a-3p and miR-23a-3p were observed in the uE of DN rats, collected between 6th-8th weeks, relative to baseline (before diabetes induction). uE- treated DN rats had significantly reduced urine albumin-to-creatinine ratio, attenuated renal pathology, and lower miR-24-3p target fibrotic/ inflammatory genes (TGF-beta, and Collagen IV), relative to vehicle treated DN rats. In uE treated rats, the renal expression of miR-24-3p, miR-30a-3p, let-7a-5p and miR-23a-3p was increased, relative to vehicle control. Patients with diabetic nephropathy had reduced renal levels, while higher uE abundance, of miRs with reno-protective potential. Reverting the urinary loss of miRs by injecting uE attenuated renal pathology in diabetic rats.